Digital fashion innovations advances in design, simulation, and industry - Sayem, Abu Sadat Muhammad (Boca Raton CRC Press, 2023)
"Digitalisation is becoming standard practice within the fashion industry, reinforced by the Covid-19 pandemic. Digital Fashion Innovations captures the state-of-art developments taking place in this multi-disciplinary field. This interdisciplinary book will appeal to professionals working in the area of textile and clothing technology, including fashion and textile technologists, those developing AR and AI for clothing end uses, and anyone interested in the business of digital fashion and textile design. It will also be of interest to scientists and engineers working in anthropometry for a variety of disciplines, such as medical devices and ergonomics"--